At the vanguard European contributions to NATO's future combat airpower - Binnendijk, Anika; Germanovich, Gene; McClintock, Bruce; Heintz, Sarah Anita (RAND Corporation, 2020)
Airpower is critical to improving NATO's defense and deterrence posture in response to Russia's aggressive actions and continued military modernization, as recognized in NATO's 2018 Joint Air Power Strategy. The capabilities of European air forces to defend allies in conflict are evolving, and the trend line in platform modernization is leading in the right direction, most critically with the introduction of fifth-generation aircraft. European allies are also beginning to invest more in personnel, training, and equipment availability. Taken together, these developments could decrease Russia's ability to achieve its operational and political-military objectives in a theater-wide conflict. The authors - drawing from interviews, an expert roundtable, and relevant literature - assess the specific opportunities and challenges that European air forces need to address to position themselves as central contributors to NATO's deterrent posture at the vanguard of any foreseeable combat air campaign. Specifically, they focus on maximalist conditions - high-intensity operations that would require rapid and large-scale application of airpower, conducted in the European theater. Their analysis examines the capabilities of the 13 allied air forces in Europe capable of making the most substantial contribution to large-scale combat operations
"RR-A311-1"--Cover page 4
Keywords: NATO; Luftwaffe; Europa; North Atlantic Treaty Organization / Air Forces; Air forces / Europe; Air power / Europe; North Atlantic Treaty Organization; Air forces; Air power; Europe